Mechanism and kinetics of chlorpyrifos co-metabolism by using environment restoring microbes isolated from rhizosphere of horticultural crops under subtropics - Kumar, Govind; Lal, Shatrohan; Soni, Sumit K.; Maurya, Shailendra K.; Shukla, Pradeep K.; Chaudhary, Parul; Bhattacherjee, A. K.; Garg, Neelima (Frontiers in Microbiology, 2022)
The indiscriminate use of organophosphate pesticide chlorpyrifos in agricultural crops causes a significant soil and water pollution and poses a serious threat to the global community. In this study, a microbial consortium ERM C-1 containing bacterial strains Pseudomonas putida T7, Pseudomonas aeruginosa M2, Klebsiella pneumoniae M6 and fungal strain Aspergillus terreus TF1 was developed for effective degradation of chlorpyrifos. Results revealed that microbial strains were not only resistant to chlorpyrifos (500 mg L-1) but also coupled with plant growth promoting characteristics as well as laccase production. PGP traits viz. IAA (35.53, 45.53, 25.19, 25.53 µg mL-1), HCN (19.85, 17.85, 12.18, 9.85 µg mL-1), Ammonium (14.73, 16.73, 8.05, 10.87 µg mL-1) production and potassium (49.53, 66.72, 46.14, 52.72 µg mL-1), phosphate (52.37, 63.89, 33.33, 71.89 µg mL-1) and zinc (29.75, 49.75, 49.12, 57.75 µg mL-1) solubilisation tests were positive for microbial strains T7, M2, M6, and TF-1, respectively. The laccase activity by ERM C-1 was estimated as 37.53, 57.16, 87.57 enzyme U mL-1 after 5, 10, 15 days of incubation, respectively. Chlorpyrifos degradation was associated with ERM C-1 and laccase activity, and the degree of enzyme activity was higher in the consortium than individual strains. The biodegradation study with developed consortium ERM C-1 showing a decreased chlorpyrifos concentration from 7th day of incubation (65.77% degradation) followed by complete disappearance (100% degradation) after 30th day of incubation in MS medium. First order degradation kinetics with linear model revealed high k -day value and low t1/2 value with ERM C-1. The results from HPLC and GC-MS analysis proved that consortium ERM C-1 was capable of completely removing chlorpyrifos by direct biodegradation.